Reinstatement of the independent specific status of Thalictrum hamatum (Ranunculaceae), with T. macrorhynchum reduced to its synonymy - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2018)
Thalictrum hamatum (Ranunculaceae) has been previously placed in synonymy with T. uncatum. Our critical examination of the original material of T. hamatum reveals that this species is actually not conspecific with T. uncatum, but with T. macrorhynchum. As T. hamatum was published earlier than T. macrorhynchum, we reduce the latter to the synonymy of the former herein. Lectotypification is proposed for T. macrorhynchum.